Bending Performance of Prestressed Continuous Glulam Beams - Nan Guo; Mingtao Wu; Ling Li; Guodong Li; Yan Zhao (Advances in Civil Engineering)
The limited transferring moment capability of Glulam (glued laminated wood) joints results in insufficient joint stiffness. Therefore, most of the connections are hinged joints. Based on the previous studies, one novel end-connection device was proposed to form prestressed continuous Glulam beams. The prestressed beams were composed of prestressed low-relaxation steel bars, the deviator block, the anchorage device, and the novel end-connection apparatus. These prestressed steel bars were tensioned by the deviator block to exert prestress. Then, 18 prestressed continuous beams and two prestressed simply supported beams were subject to the bending tests to explore the impact of reinforcement ratio and prestress on the prestressed Glulam beams from aspects such as failure modes, bearing capacity, load-deflection relationship, and load-strain relationship. The results show that, given the same prestress level, compared with beams with a reinforcement ratio of 1.92%, the bearing capacity of beams with a reinforcement ratio of 3.84% and 5.76% is increased by 20.3%–29.4% and 30.51%–36.36%, respectively. Given the same reinforcement ratios, compared with beams without prestressing, the bearing capacity of beams with a prestressing force of 7 kN and 14 kN is increased by 2.39%–10.14% and 6.49%–13.26%, respectively. In addition, compared with simply supported beams, the bearing capacity of continuous beams is increased by 40%, and the deformation is reduced by 13%. Therefore, as a novel prestressed beam, the bending performance of Glulam beams can be improved effectively.